2014
DOI: 10.3109/19401736.2014.908470
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence of Culter compressocorpus

Abstract: In this study, the complete mitochondrial genome of Culter compressocorpus was detected and annotated. The circular mtDNA molecule was 16,623 bp in length which contains 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and the non-coding control region (D-loop). Its total protein-coding genes content is 68.67% in whole mitochondrial genome. The mitochondrial genome can contribute to the studies on geographical distribution and genetic diversity of C. compressocorpus resources, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…We found that two protein-coding genes (Nad3 and Nad4) had the incomplete stop codon TA, and the other 2 genes ended with the incomplete stop codon T (Cox2 and Cob). These results were the same as for Culter compressocorpus 12) and Culter recurviceps 13) .…”
Section: Resultssupporting
confidence: 77%
“…We found that two protein-coding genes (Nad3 and Nad4) had the incomplete stop codon TA, and the other 2 genes ended with the incomplete stop codon T (Cox2 and Cob). These results were the same as for Culter compressocorpus 12) and Culter recurviceps 13) .…”
Section: Resultssupporting
confidence: 77%